Development of Textbook Loan Management System (TLMS) / Ainul Azila Che Fauzi … [et al.] - Che Fauzi, Ainul Azila; Haikal, Afiq; Fauzi, Auni; Mohamad Arifin, Mohamad Syauqi (Unit Penerbitan, UiTM Kelantan, 2022)
Technology has played an essential influence in the development and expansion of education around the world. However, not all students will enjoy the benefits and gain equal access to knowledge through online learning. There is still limited internet access, limited number of devices causes them to share those devices with other family members, as well as devices that do not support the display of content on websites and smartphone applications. It is indeed impossible to ignore the value of textbooks because textbooks serve as a reference tool for students both at school and at home. However, even though it has been operating for a long time, textbook management system still operates manually. The biggest issues with the manual approach are the inefficiency of manually collecting students' data, storing the data securely and keeping track of lost textbooks. This manual data storing poses the risk of losing the forms because in a school, there are thousands of students who are involved in this process. It is impossible to ensure the data is kept safe because the same form must be marked and returned twice, during the borrowing and returning processes. As a result, it is difficult to determine the textbook inventory and miscalculation may occur as well as making mistakes when ordering textbooks. Teachers also might have difficulties in finding those who lost the textbooks. The aim of this research is to replace the existing manual system with a computerized Textbook Loan Management System (TLMS), also known as Skim Pinjaman Buku Teks (SPBT). This system will help teachers who oversee SPBT, also known as SPBT teachers, to manage the whole process and data involved during the borrowing and returning of textbooks. This project will use a barcode scanner to scan the International Standard Book Number (ISBN) barcode at the back cover of the textbooks to minimize the time consumed for the whole process.